Gait patterns comparison of children with Duchenne muscular dystrophy to those of control subjects considering the effect of gait velocity - Gaudreault, Nathaly; Gravel, Denis; Nadeau, Sylvie; Houde, Sylvie; Gagnon, Denis (Gait & posture, 2010)
3D analysis of the gait of children with Duchenne muscular dystrophy (DMD) was the topic of only a few studies and none of these considered the effect of gait velocity on the gait parameters of children with DMD. Gait parameters of 11 children with DMD were compared to those of 14 control children while considering the effect of gait velocity using 3D biomechanical analysis. Kinematic and kinetic gait parameters were measured using an Optotrak motion analysis system and AMTI force plates embedded in the floor. The data profiles of children with DMD walking at natural gait velocity were compared to those of the control children who walked at both natural and slow gait velocities. When both groups walked at similar velocity, children with DMD had higher cadence and shorter step length. They demonstrated a lower hip extension moment as well as a minimal or absent knee extension moment. At the ankle, a dorsiflexion moment was absent at heel strike due to the anterior location of the center of pressure. The magnitude of the medio-lateral ground reaction force was higher in children with DMD. Despite this increase, the hip abductor moment was lower. Hip power generation was also observed at the mid-stance in DMD children. These results suggest that most of the modifications observed are strategies used by children with DMD to cope with possible muscle weakness in order to provide support, propulsion and balance of the body during gait.